METHODS APPLIED IN TRANSLATING THE SECOND CHAPTER OF KENNETH GRAHAME’S THE WIND IN THE WILLOWS = Các phương pháp dịch được áp dụng trong việc dịch chương hai của tác phẩm “the wind in the willows » của Kenneth Grahame - Nguyễn, Ngọc Huyền (2020)
In an attempt to contribute to gain more insights into translation methods in literary translation, this research aims to investigate the use of translation methods by different professional translators in translating Kenneth Grahame‟s The Wind in the Willows. Specifically, the study focuses on naming exactly every translation methods used and identifying the frequency of each as well as their effectiveness. Particularly, as emerged from the findings, the difference between literal translation approach (indicated with the dominant use of literal translation method) and non-literal one (reflected by the use of other non-literal methods, namely semantic, communicative, faithful and free translation methods) has been meticulously analyzed and discussed. The methodological approach of the study is both quantitative and qualitative.